Subjectivity as an element for nursing care - Herrera Paredes, José Manuel (2023)
For nursing professionals, care planning is important if they want to obtain favorable results for the people they care for, which is why when generating care planning, they should reflect on the subjective aspects that allow the person to visualize the world and that result in the generation of actions or behaviors that favor or harm their health, otherwise the effectiveness of care interventions could be short-lived or short-lived. This situation is what has motivated the creation of this brief consideration of what subjectivity is and how it constitutes the human being as a being in order to understand its implications in health-disease processes.